PENERAPAN METODE REWARD AND PUNISMENT DALAM MENINGKATKAN PRESTASI PESERTA DIDIK PADA MATA PELAJARAN AL QURAN HADITS - Aidah Aidah; Mustafiyanti Mustafiyanti; Naswa Nadia (Journal of Innovation Research and Knowledge, 2023)
Application of Reward and Punishment in Increasing Student Learning Achievement in Al-Quran Hadith Subjects at Madrasah Aliyah Negri 01 Ogan Ilir, Thesis, Department of Islamic Religious Education, Faculty of Tarbiyah Sciences, Al-Quran Islamic Institute, Al-Ittifaqiah Indralaya. The aim of this research is to find out and reveal how reward and punishment are applied in improving student learning achievement in the Al-Quran Hadith subject at Madrasah Aliyah Negeri 01 Ogan Ilir. In this research the author used qualitative research, qualitative descriptive methods. The results of this research show that the application of rewards and punishments in improving students' learning achievement in the Al Quran Hadith subject at Madrasah Aliyah Negri 01 Ogan Ilir was carried out to motivate students in ongoing learning, teach a sense of responsibility for what has been done, and get used to discipline. There are two forms of reward, namely non-material such as smiles, thumbs up and applause. Material rewards include giving candy, pencils, drawing paper and stars. Meanwhile, the form of punishment is preventive punishment, namely by implementing rules and regulations and repressive punishment, namely giving punishment to students. For example, if a student says something impolite, he or she is given a sanction of saying istighfar 10 to 100 times and his/her goodness star/achievement star is taken away. Another violation is that if you do not want to follow the teacher's directions, you will be given a sanction from standing in front of the class while studying or even being expelled from the class. If you are late, you will be punished by praying alone while standing in front of the class.